Energy efficiency on public street lighting using LTE lamp based IoT control - Lubis, Faisal; Sundawa, Bakti Viyata; Cholish, Cholish; Abdullah, Abdullah (Jurnal Mantik, 2025)
Nowadays, The Medan city has developed public street lighting along the protocol highways. The government has spent billions bugdet to readiness. The estimated electrical consumption for public street lighting will be 47.06 MW by 2025. Therefore, energy efficiency is required to complete the system of public street lighting. This research use LTE lamp to control electrical consumption for lamps. There are 4 main components, namely LTE Lamp Controller, which is including a LoRa component, light sensors BH1750, SIM card, and fuzzy logic program. Cloud server as a storage for measurement data. Monitoring devices as laptop or smartphone. GSM network as interface networking between LTE lamp controller and cloud server. The sunlight intensity affected to the dimming value of the lamp. It uses fuzzy logic to regulates the switching of lamps. LTE lamp controller supports the dimming mode such as 0-10V dimmer. This voltage directly correlates to the light output. At 10 Volt, the lamp should produce 100% light. At 0 Volt, 0% lighting output or off. Based on the result, The highest of sunlight intensity is 7796 lux generating the voltage of 1 Volt (lamp off). The lowest of sunlight intensity is 1028 lux generating the voltage of 7 Volt (lamp on